Desenvolvimento de coração bioartificial a partir de arcabouço de matriz descelularizada e cardiomiócitos neonatais - Taufner, Gabriel Henrique (2018)
Cardiovascular diseases are the leading cause of death in the world. It is estimated that 50% of patients with heart disease do not respond satisfactorily to therapeutic approaches and require a heart transplant to replace the diseased heart with a healthy one. The objective of this work was to obtain and characterize structurally and functionally MEC decellularized from neonatal mouse heart. We obtained MEC of neonatal mice through a decellularising approach using 0.2% SDS, which was able to remove 98.5% of native DNA. We demonstrate the maintenance of ECM molecules through spectrophotometric measurements, histochemical and immunohistochemical staining. We observed that the decellularized MEC was able to provide support to the cell population used for the recellularization, and was not able to induce inflammatory activity when transplanted into immunologically competent animals, suggesting that decellularization was effective in removing molecules responsible for triggering the immune response of host. MEC with a neonatal developmental age can provide valuable information in processes related to tissue regeneration and repair, since some molecules have intense activity in this period, contrary to what had previously been observed in relatively older tissues.